Stress, coping strategies and academic achievement in teacher education students - Gustems-Carnicer, Josep; Calderón, Caterina; Calderón-Garrido, Diego (European Journal of Teacher Education, 2019)
University students experience stress, and how they cope with this stress affects their academic achievement. This study examined stress in teacher education students and had three objectives: to describe different degrees of stress and coping styles; to study the relationship between stress, coping strategies and academic achievement; and to examine whether increased age can moderate the effects of stress on academic achievement in 334 university-students. There were three main findings: many students experienced stress and used avoidance coping strategies; the students who were under less stress and engaged less in cognitive avoidance and more in problem-focused coping were also the students who made more academic achievement; and students under more stress performed worse, but with age stress affected performance less. In teacher education students, it is important to recognize and address the harmful effects of stress on well-being and academic achievement, to avoid long-term problems in professional and personal life.
Keywords: academic achievement; coping strategies; stress; teacher education students; Scopus; JCR